Implementation and control of a double-input DC/DC converter for PEMFC/battery hybrid power supply - Xian, Liang (2013)
Proton exchange membrane fuel cell (PEMFC) has a time-delay feature on its electrical characteristic. So other energy sources with relatively higher response rate and better dynamic performance is necessary for assisting and sharing responsibility with PEMFC in hybrid power supply system. Multi-input DC/DC converter, which has higher efficiency, less component count, lower cost and simpler control method, is a promising candidate for developing multi-source hybrid system. In this paper, a double-input buck converter (DIBC) topology and its control method are proposed and designed. The target of regulating both the DIBC output voltage and output current of PEMFC is proved to be feasible. A prototype of PEMFC/battery hybrid power supply system based on the proposed DIBC topology is developed for verifying the correctness of the presented theory and design. Experimental result shows ideal output characteristics and control effect of the prototype.